Of time and lamentation: reflections on transience - Tallis, Raymond (Agenda Publishing, 2017)
Time's mysteries seem to resist comprehension and what remains, once the familiar metaphors are stripped away, can stretch even the most profound philosopher. In Of Time and Lamentation, Raymond Tallis rises to this challenge and explores the nature and meaning of time and how best to understand it. The culmination of some twenty years of thinking, writing and wondering about (and within) time, it is a bold, original, and thought-provoking work. With characteristic fearlessness, Tallis seeks to reclaim time from the jaws of physics. For most of us, time is composed of mornings, afternoons, and evenings and expressed in hurry, hope, longing, waiting, enduring, planning, joyful expectation, and grief. Thinking about it is to meditate on our own mortality. Yet, physics has little or nothing to say about this time, the time as it is lived. The story told by caesium clocks, quantum theory, and Lorentz coordinates, Tallis argues, needs to be supplemented by one of moss on rocks, tears on faces, and the long narratives of our human journey. Our temporal lives deserve a richer attention than is afforded by the equations of mathematical physics.The first part of the book, "Killing Time" is a formidable critique of the spatialized and mathematized account of time arising from physical science. Part 2, "Human Time" examines tensed time, the reality of time as it is lived: what we mean by "now", how we make sense of past and future events, and the idea of eternity